Acute and persistent symptoms of COVID-19 infection in school-aged children: a retrospective study from China - Honglin Wang; Fangfang Lu; Xiuxian Ni; Rijing Luo; Linxiang Chen; Jing Yuan; Zhen Zhang; Qiuying Lv (BMC, 2024)
Abstract Background The long-term sequelae of Coronavirus disease 2019 (COVID-19) in children are unclear. We investigated COVID-19 symptoms in school-aged children to determine their impact on patients and their families. Methods This cross-sectional study, conducted on February 25-28, 2023, selected a representative kindergarten and 9-year school from Shenzhen, China. There were randomly two classes each for the 12 grades from kindergarten to junior high school. The school-aged children were aged 3-16 years. Literate parents completed an online questionnaire related to their children's COVID-19 symptoms since December 1, 2022. Descriptive statistics were computed as necessary. Univariate and multivariable linear regression analyses were performed, and variables with a p-value < 0.05 were considered to have a significant association with the subjective feeling scores for COVID-19 infection. Results We included 936 school-aged children, with a COVID-19 infection rate of 68.5%. The prevalence of LC 28 (illness with symptoms lasting for 28 days) was 3.4%. During acute infection, the median number of the 641 children's symptoms was 3.0 (IQR: 1.0-5.0) and the median score of subjective feelings was 15.0 (IQR: 11.0-24.5). The top three symptoms were fever, cough/expectoration, and rhinobyon. Age of 13-16 years (adjusted beta: 3.60, 95% CI: 0.32-6.88) and comorbidities (adjusted beta: 3.47, 95% CI: 1.20-5.73) were independently associated with higher subjective feelings (p < 0.05). The top three characteristics associated with LC 28 were alopecia (33.3%, 5/15), cognitive dysfunction (29.2%, 7/24), and emotional problem (28.6%, 6/21). Conclusions Children with COVID-19 have a short duration of symptoms and milder symptoms, so they can self-medicate to minimize hospital crowding. Children with basic diseases require prompt attention. Although LC 28 is uncommon in children, mental and psychological problems after COVID-19 recovery should not be ignored.